Are Breaks Better? A Comparison of Breaks Are Better to Check-In Check-Out. - Majeika, Caitlyn E.; Wehby, Joseph H.; Hancock, Eleanor M. (Behavioral Disorders, 2022)
Identification and validation of effective Tier 2 interventions that address a wide range of student-level factors is critical to the sustainability of positive behavior interventions and supports (PBIS). Within the context of Check-in Check-out (CICO), function of behavior affects outcomes for many students, especially for those who engage in problem behavior to escape from tasks. Therefore, more research is needed to understand if and how we can support students with escape-maintained behavior. Breaks are Better (BrB) is a modified version of CICO that includes a system for taking breaks. The current research on BrB is limited but promising. The purpose of this study was to compare the effectiveness of CICO to BrB. Using a multitreatment design, we compared the effects of each intervention by measuring problem behavior and academic engagement across five elementary students who engaged in problem behavior to escape from tasks. Overall results were mixed and ranged from strong effects of BrB to no differential effects. However, despite the results, teachers and students consistently rated BrB as being a more preferable intervention. We conclude with limitations and implications for practice.